2016
DOI: 10.1016/j.cgh.2015.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcomes of Patients Receiving a Magnetic Sphincter Augmentation Device for Gastroesophageal Reflux

Abstract: Augmentation of the lower esophageal sphincter with a magnetic device provides significant and sustained control of reflux, with minimal side effects or complications. No new safety risks emerged over a 5-year follow-up period. These findings validate the long-term safety and efficacy of the magnetic sphincter augmentation device for patients with GERD. ClinicalTrials.gov no: NCT00776997.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
123
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(133 citation statements)
references
References 36 publications
6
123
0
4
Order By: Relevance
“…Both revisional operations were performed without difficulty, confirming previous reports on the safety and feasibility of laparoscopic anti-reflux surgery after TF [25]. Recently, a study discussing another more invasive anti-reflux procedure purported that the rate of reoperation following TF could range from 11.5 to 52.6 % [26], citing reports from Europe where earlier iterations of the device and technique had been used [2730] in a suboptimally selected patient population which included large hiatal hernias and Hill grade III and IV. In contrast, in the TEMPO trial and other recent randomized controlled TF trials [1215], all patients received a standardized TF 2.0 procedure with a rotational component, as described by Bell and Cadière [11].…”
Section: Discussionsupporting
confidence: 77%
“…Both revisional operations were performed without difficulty, confirming previous reports on the safety and feasibility of laparoscopic anti-reflux surgery after TF [25]. Recently, a study discussing another more invasive anti-reflux procedure purported that the rate of reoperation following TF could range from 11.5 to 52.6 % [26], citing reports from Europe where earlier iterations of the device and technique had been used [2730] in a suboptimally selected patient population which included large hiatal hernias and Hill grade III and IV. In contrast, in the TEMPO trial and other recent randomized controlled TF trials [1215], all patients received a standardized TF 2.0 procedure with a rotational component, as described by Bell and Cadière [11].…”
Section: Discussionsupporting
confidence: 77%
“…34 In the only study that reported healing of esophagitis, Ganz et al found healing of esophagitis in 76.5% of patients at 5 years. 38 Complete cessation of all PPI use was achieved in 71.4–85.3%, with 75.3% of patients reporting complete cessation and 9.4% reporting on demand PPI use at longest follow-up of 5 years. 3438 …”
Section: Resultsmentioning
confidence: 90%
“…38 Complete cessation of all PPI use was achieved in 71.4–85.3%, with 75.3% of patients reporting complete cessation and 9.4% reporting on demand PPI use at longest follow-up of 5 years. 3438 …”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…A single-center study [21] and a multicenter single-arm study, [22] enrolling 100 patients each, evaluated the long-term results of magnetic augmentation and showed that the procedure provides significant and sustained control of reflux with minimal side-effects or complications up to 6 years of follow-up. However, no randomized trials exist that can validate the effectiveness of the LINX and reliably compare its results with other established surgical therapies.…”
Section: Discussionmentioning
confidence: 99%